Childfree in the Lens of Islamic Jurisprudence: Women’s Reproductive Rights between Classical and Contemporary Fiqh - Nerisma Eka Putri; Riski Hariyadi; Ibnu Najah; Rikki Arisandi; Abubakar Muhammad Babayya; Mustiah Mustiah (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2025)
In religious conception, marriage is the law chosen by God as a means for humans to have offspring. However, not all married couples have the desire to have children. The unwillingness to have children is often referred to as childfree. Childfree is the desire not to have children in the future. In Indonesia, the term childfree began to attract attention on social media since Analisa Widyaningrum, a clinical psychologist, invited Gita Savitri, so that this opinion eventually reaped pros and cons in various circles. Therefore, researchers are interested in examining how childfree is viewed based on classical and contemporary fiqh studies. This research uses library research with a qualitative approach, namely to examine the phenomenon of childfree based on women's reproductive rights, then examine childfree based on historical facts from classical fiqh through the works of classical Ulama' and childfree based on contemporary fiqh, by adjusting the opinions of Ulama' in accordance with the reality of modern times. It can be found that according to the reproductive rights of childfree women, as stated by Masdar, emphasizing that a wife has the right to want to get pregnant and determine the number of children she wants, such things should be the free choice of the individual concerned. Any party has no right to intervene and even impose their will in any way and for any reason. Because in the future those who bear the risk are of course both parties, especially a wife. Furthermore, based on classical fiqh, Childfree can be equated with the term 'Azl, namely rejecting the existence of a child before it has the potential to exist and this is not punished as haram, but rather punished as makruh based on the Book of Ihya 'Ulum al-Din. Furthermore, childfree based on contemporary fiqh there is also no prohibition either in the Qur'an or hadith, the agreement of husband and wife not to have children is allowed especially on the basis of concerns or because of illness, this is also the same as classical fiqh where the problem of childfree is qiyaskan with the problem of Azl.